Statistical approach for the evaluation of household solid waste generation in Peruvian households: 2014–2021 - Padilla-Vento, Jorge L.; Soria, Juan J. (Frontiers in Applied Mathematics and Statistics, 2025)
This study addresses the evaluation of the generation of domestic solid waste in Peruvian households using statistical techniques and the SEMMA and PCA data mining methodology. The objective is to explore how waste management, population and the Per Capita Generation index PCG index per capita influence the production of this waste in Peruvian departments. The sample was obtained from the database of annual reports submitted by district and provincial municipalities to MINAM through the Information System for Solid Waste Management (SIGERSOL), including data from the 24 departments of Peru, with a total of 14,852 records organized in 196 registration forms. Statistical techniques and the adaptation of the SEMMA methodology were applied together with the Principal Component Analysis (PCA) to examine the impacts of the accumulation of household solid waste in Peru. This study showed that the first component accounts for 80.2% of the inertia. Combining the first two components accounts for 99.8% of the total variation, suggesting that most of the meaningful information can be maintained using only two dimensions. Welch’s ANOVA showed significant differences in domestic solid waste generation among Peruvian departments [F (6, 94.310) = 790.444; p = 0.0, p < 0.05]. In addition, a square Eta of 99.09% revealed a very large effect size, indicating that the amount of population explains 99.09% of the variation in the generation of this waste between the departments. The PCG index had a moderate effect, suggesting the need for further studies to explore the underlying causes of regional differences and assess the effectiveness of the waste management measures implemented. A positive relationship was found between the production of Domestic Solid Waste (DSW) and the number of inhabitants. Lima stood out with the highest average of DSW 13220.47 tons and the PCG index of 50%. Using Ward’s method, three groups were obtained and PCA was applied to each group. In the Group, Lambayeque 5616.48 tons, Loreto 2946.44 tons and San Martín 1596.07 tons registered the highest DSW averages, while Amazonas 441.1 tons obtained the lowest. Ucayali 60%, Loreto 58% and San Martín 57% showed the highest PCG indexes. In Group b, Ayacucho 701.81 tons had the highest average DSW and Apurimac 497 tons the lowest. Tacna and Apurimac with 44% and Moquegua 43% registered the highest PCG indexes, while Huancavelica 42% and Pasco 41% had the lowest. In Group C Piura 4476.53 tons and La Libertad 3478.46 tons showed the highest DSW averages, while Huánuco 859.41 tons and Cajamarca 812.74 tons registered the lowest. Ica and Piura led with an average PCG of 48%, while Puno and Junín with 43% had the lowest values.